Camouflage uncovered: what should happen next?. (1st March 2023) - Wilton, Tim; Skinner, John A.; Haddad, Fares S.
Abstract : Recent publications have drawn attention to the fact that some brands of joint replacement may contain variants which perform significantly worse (or better) than their 'siblings'. As a result, the National Joint Registry has performed much more detailed analysis on the larger families of knee arthroplasties in order to identify exactly where these differences may be present and may hitherto have remained hidden. The analysis of the Nexgen knee arthroplasty brand identified that some posterior-stabilized combinations have particularly high revision rates for aseptic loosening of the tibia, and consequently a medical device recall has been issued for the Nexgen 'option' tibial component which was implicated. More elaborate signal detection is required in order to identify such variation in results in a routine fashion if patients are to be protected from such variation in outcomes between closely related implant types. Cite this article: Bone Joint J 2023;105-B(3):221–226.